The Disappearance of Fibrin from the Pulmonary Vessels in Experimental Fat Embolism - Saldeen, T (Thrombosis and Haemostasis, 1969)
The background mechanism for the disappearance of intravascular fibrin from the lungs in connection with pulmonary fat embolism in the rat was studied.The reticulo-endothelial system did not appear to play an important role in the disappearance of fibrin. Premedication of the animals with trypan blue had only slight influence on this disappearance, and the capacity of RES for phagocytizing 131I-denatured albumin was not diminished.Treatment of the rats with a plasminogen activation inhibitor (EACA) resulted in a protracted presence of intravascular fibrin deposits, indicating a role of fibrinolysis in the elimination of the fibrin.In connection with experimental fat embolism induced by fracture, an increase was observed in the plasminogen activator concentration in the blood, but when the fat embolism was induced by intravenous injection of homogenized adipose tissue, this activator decreased. At an early stage following intravascular coagulation in the lungs there was an increased fibrinolytic activity in the lung. These results indicated that the disappearance of fibrin is caused by local fibrinolysis in the lung.Twenty-four hrs after the induction of the fat embolism an increase in the plasminogen activator inhibitors in the blood and a decrease in the fibrinolytic activity in the lung was observed. The significance of this inhibition of the fibrinolytic system for the understanding of the fat embolism syndrome is discussed.